Reliance of the Strength of a Sandstone on Petrographic Attributes: A Preliminary Study - Yar, Mustafa; Meraj, Asad; Basit, Abdul; Naseem, Fawad; Khan, Mumtaz Ali (The Nucleus, 2023)
For the present preliminary geotechnical investigation, sandstone from Dandot Formation of Permian age has been selected with eighteen samples that were collected for detailed petrographic analysis while three bulk samples were collected for geotechnical analysis. On the basis of grain size sandstone of Dandot Formation was divided into three parts. The lower part was mostly very fine, middle part was generally fine and upper part was of medium grain. Texturally and mineralogically the sandstone was sub-mature. Framework grains in the studied samples essentially consisted of variable amount of quartz (62 to 73%), feldspar (10 to 19%), and rock fragments (3 to 6%). Accessory minerals include muscovite, biotite, iron ore minerals, zircon and glauconite. The cement type in the samples was clayey ferruginous. The modal composition of the sandstone falls in the category of Arkose. The strength test including unconfined compressive strength, unconfined tensile strength, shear strength, specific gravity, and water absorption tests were employed on the rock samples to assess their geotechnical utilities. After evaluating these properties, the acquired test results indicated that the sandstone is very weak and hence cannot be used for construction purposes.